Students’ Experience on Studying in Semester System - Luitel, Ramesh Prasad (Journal of Research and Development, 2026)
The semester system has emerged as a significant reform in higher education in Nepal, aiming to enhance the quality of teaching, learning, and evaluation processes. Unlike the traditional annual system, which primarily depends on final examinations, the semester system emphasizes continuous assessment, active participation, and the holistic development of learners. This study explores the lived experiences of students studying under the semester system in order to understand its effectiveness and challenges from the learners’ perspective. This research adopts a qualitative approach, specifically a phenomenological design, to capture the real-life experiences of students. Five students from the fourth semester were purposively selected as participants. Data were collected through in-depth interviews conducted in two phases to ensure depth and clarity. The collected data were transcribed, coded, and analyzed using thematic analysis. The findings of the study reveal three major themes. First, the semester system functions as a learning platform that promotes life skills such as communication, collaboration, critical thinking, and problem-solving. Second, students experience both pressure and satisfaction due to continuous assignments and evaluations. Third, the semester system fosters a culture of continuous learning and academic engagement. The study concludes that the semester system is more effective than the annual system in promoting student-centered learning, continuous improvement, and skill development. However, its success depends on proper implementation, availability of resources, and institutional support.